ILMU DAN ORANG BERILMU DALAM AL-QUR’AN: MAKNA ETIMOLOGIS, KLASIFIKASI, DAN TAFSIRNYA - Ferry Muhammad Siregar, Surahman Amin dan (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
This paper aims at discussing about knowledge (Ã¢â‚¬Ëœal-Ã¢â‚¬Ëœilm) and scholar (al-Ã¢â‚¬ËœÃ„Âlim) in the QurÃ¢â‚¬â„¢an with a focus onÃ‚Â their etymological meanings, classification and interpretation (tafsÃ„Â«r). In addition, it examines the words ofÃ‚Â verses related to al-Ã¢â‚¬Ëœilm and al-Ã„Âlim, being analyzed by the theory of QurÃ¢â‚¬â„¢anic exegesis, especially tafsÃ„Â«r mauÃ¡Â¸ÂÃ…Â«Ã¢â‚¬â„¢Ã„Â«.Ã‚Â It faund that the al-Ã¢â‚¬Ëœilm is a real knowledge on an object in accordance with its conditions and characters. Al-Ã‚Â Ã¢â‚¬â„¢ilm can be divided into two types, i.e. kasbÃ„Â« (gained knowledge) and ladunnÃ„Â« or mawhibah (gifted knowledge).Keywords: Knowledge, TafsÃ„Â«r, Ã¢â‚¬ËœUlamÃ„ÂÃ¢â‚¬â„¢